Efficacy of imiquimod 5% cream for persistent human papillomavirus in genital intraepithelial neoplasm - Fang-Ping Chen (Elsevier, 2013)
Objective: To assess the clinical response to imiquimod 5% cream in patients with persistent human papillomavirus (HPV) infection after treatment of genital intraepithelial neoplasia. Materials and Methods: Imiquimod 5% cream was applied to treat 76 women with persistent HPV after surgical therapy for cervical or vaginal intraepithelial neoplasia (CIN or VAIN). One sachet of cream was placed in the cervical os and vagina with an applicator twice weekly for 8 weeks. Repeated HPV evaluation and Papanicolaou (Pap) smear and/or biopsy were performed 3 months following treatment completion. Results: In total, 58 of the 76 patients (76.3%) were clear of HPV infection and had normal Pap smears after administration of imiquimod cream. Although atypia or mild dysplasia was noted in 15 of the 18 patients (83.3%) with persistent HPV infection after imiquimod cream treatment, the degree of severity was noticeably less than the initial diagnosis in most of these patients. Persistent HPV positivity was observed in 12 of the 64 patients (18.8%) with CIN and 6 of the 12 patients (50.0%) with VAIN. Conclusion: Topical imiquimod 5% cream may be beneficial in most cases of genital intraepithelial neoplasia, especially CIN, with persistent HPV following surgical treatment.